NALAR ISLAM PROGRESIF DALAM FIQIH UMAR BIN KHATTAB - Nurul Fadzilah; Mahathir Muhammad (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2023)
The presence of progressive Islam in the midst of the rapid dynamics of change has become a solution to problems that are considered to have not yet been answered. Significant currents of change demand Islam as a religion that is ahmahan lil alamin always relevant to various times and circumstances. In short, the Al-Qur'an with the jargon of sahih likuli age wa food continues to be implemented, therefore it is necessary that in this article the author will explain the progressive Islamic reasoning of the Prophet's closest friend, Umar bin Khattab. Umar bin Khattab was known for his strict adherence to Islamic law and his efforts to promote justice and equality. The role of Umar bin Khattab in the formation of the science of jurisprudence was very large. His contribution cannot be denied, it is even said that fiqh in general is the result of legal ijtihadijtihad from Umar bin Khattab. The principles of progressive fiqh of Umar bin Khattab are still the starting point in reviewing new laws in the flow of development and dynamics of science.